Transferability of bioprocessing modes for recombinant protease production: from fed-batch to continuous cultivation with Bacillus licheniformis - Stefan Kittler; Fabian Müller; Mohamed Elshazly; Georg Benjamin Wandrey; Tobias Klein; Andreas Daub; Oliver Spadiut; Julian Kopp (BMC Biotechnology)
Abstract Background Proteases are essential in various industries due to their unique substrate specificities and robustness in different operational conditions. Bacillus strains consist of a genotype favorable for rapid growth whilst secreting enzymes extracellularly, thereby simplifying recombinant protease production. Despite the widespread use of batch and fed-batch fermentations for their ease and robustness, these cultivation types are often marred by significant energy requirements and prolonged downtimes. The switch towards continuous cultivation methods promises reduced carbon footprints and improved equipment efficiency. Yet, research focusing on Bacillus strains is limited, therefore we aimed to establish a continuous cultivation as a competitive alternative to fed-batch. Results Therefore, this study aimed to explore the potential of chemostat cultivations for producing a protease from Bacillus licheniformis utilizing a derepressed induction system, and comparing specific productivities and space-time yields to fed-batch cultivations. The continuous cultivations were described in a hybrid model, considering the effect of productivity as function of the applied dilution rate as well as the generation time. The workflow of this study demonstrates that screenings in a fed-batch mode and chemostat cultivations conducted at the same growth rate, result in different specific productivities for derepressible systems. Conclusion The results of this study highlight that the feeding rate’s impact on specific productivity varies significantly between fed-batch and chemostat cultivations. These differences suggest that fed-batch screenings may not be adequate for developing a continuous process using a derepressed promoter system in B. licheniformis. Although the space-time yield of fed-batch cultivations has not been surpassed by stable continuous operations—achieving only a third of the highest space-time yield observed in fed-batch—valuable mechanistic insights have been gained. This knowledge could facilitate the transition towards a more sustainable mode of cultivation for industrial protease production.